Factors of congenital malformations of dentoalveolar anomalies in the children's population of Kizlyar (environment of trouble) and Khasavyurt (environment of well-being) - F. I. Osmanova; I. N. Osmanov; T. F. Kosyreva (Эндодонтия Today)
Analysis to identify the relationship between the unfavorable living environment and congenital malformations of dental anomalies in the children's population of Kizlyar (the environment of disadvantage) and Khasavyurt (the environment of well-being).Materials and methods. To identify the main causes of the appearance of congenital clefts, we conducted a survey of 125 parents of children with questions included in the questionnaire: Full name, gender, date of birth, address, nationality, what is the pregnancy, whether the mother took medication in the first 3 months of pregnancy, the level of hemoglobin and infectious diseases during pregnancy, whether there were cases (heredity).Results. Dates from 125 medical histories for 2017-2019 with different types of congenital cleft lip and palate showed that in 59 children, the chemical factor was the cause of the disease, since one of the parents worked in agriculture or an industrial enterprise with a chemical bias, for genetic reasons, 15 children; viral colds-22 children, anemia of pregnant women-25 cases. 35 patients with the chemical factor were born in Kizlyar, only 5 patients from Khasavyurt. Conclusions. The high level of morbidity of the child population in Kizlyar indicates the need to develop and implement recommendations for the organization of preventive and medical-dental care for adolescents and children from an early age.